Egyptian film censorship: Safeguarding society, upholding taboos - Dina Mansour (Alphaville: Journal of Film and Screen Media, 2012)
Films are a representation and manifestation of culture; yet, since the early days of filmmaking public debates have questioned whether “the motion picture industry was morally fit to control the content of its own products” (Robichaux). Today, the Arab world is plagued by the same dilemma. In a region where government censorship is the norm, heavy restrictions are imposed on locally produced films as a means of “safeguarding” public norms, religion and culture. Also problematic in today’s globalised world is the influx of foreign films into local markets, which not only defy public norms, but also represent cultural values and traditions that are quite alien to societies that have been inherently religious and conservative. Against this background, this article aims to analyse the role of censorship in Egypt with regard to the relationship between cinema and culture—a relationship often overlooked and perhaps intentionally ignored. In doing so, it will examine how censorship has traditionally been used as a tool to control the representation of existing social and cultural realities and to define cultural and religious norms, thus also affecting the normative context.